Prevalence and incidence of sarcopenia in Swiss postmenopausal women: findings from the OsteoLaus Cohort (Swiss Medical Weekly, 2025)
STUDY AIMS: Sarcopenia is a progressive, age-related loss of muscle mass, strength and function. Given the ageing population and the adverse outcomes associated with sarcopenia, monitoring its epidemiology is particularly important. This study aimed to describe sarcopenia prevalence, 5-year incidence and agreement between definitions using the latest operational criteria in Swiss postmenopausal women.METHODS: Postmenopausal women from the last 5 years of the CoLaus/OsteoLaus prospective population-based cohort were included based on complete case analysis (April 2015 to October 2022; Lausanne, Switzerland). We assessed appendicular lean mass via Dual X-ray Absorptiometry (GE Lunar iDXA), handgrip strength using a Jamar Dynamometer and 6-metre gait speed at multiple visits. Sarcopenia was defined based on handgrip strength and/or appendicular lean mass and/or gait speed using 11 definitions, including that from the European Working Group on Sarcopenia in Older People (EWGSOPII, 2019). Prevalence was measured as the number and rate of sarcopenic cases at the last visit, while incidence was measured as the number and rate of new sarcopenic cases over 2.5 or 5 years.RESULTS: A total of 930 women were included, with a mean (standard deviation) age of 72.9 (6.9) years, BMI of 25.7 (4.8) kg/m2, appendicular lean mass 16.8 (2.5) kg, handgrip strength 21.2 (5.5) kg, gait speed 1.1 (0.2) m/s. Sarcopenia prevalence based on EWGSOPII definitions ranged from 2.2% to 5.7%, while other definitions varied from 0.5% to 13.4%. The 5-year incidence rates based on EWGSOPII were 1.9% to 4.7%. Prevalence and incidence increased significantly between the lowest and highest age tertiles (Fisher’s exact test, p